(untitled) (Journal of Economic Research & Business Administration, 2016)
The requirement for use of marketing methods is becoming a topical issue in Kazakhstan’s economy. The development of innovative marketing technologies in any sector of our country gives enterprises great opportuni ties, including the achievement of high competitive ability in market, make customers stare with unusual offer, creating new products and services and its off take, as well as entry with innovative products and services into in ternational markets. Altogether innovative marketing technologies result in development of our country’s economy. In this article considered the fea tures of innovative marketing technologies. The content and possibilities of the traditional and innovative marketing technologies in this article. The scope of application of the innovative marketing technologies’ possibility defined by outcomes showed. Also, regarding applying in practice and researching new methods of marketing foreign experiences considered.